The Perception of Lack of Security of ‎Tourist in the Latacunga City and Its ‎Impact on Tourism Demand - BRAZALES HERRERA, Diego Fabricio; CABEZAS MEJÍA‎, Edison Damián; SANTAMARÍA TORRES, Belén Johana (Journal of Environmental Management and Tourism; Vol 10 No 6 (2019): JEMT Volume X Issue 6(38) Fall 2019DO - 10.14505//jemt.v10.6(38).24, 2020)
There are several reasons for traveling to a tourist destination, which depend on the personality and objectives, however a key factor ‎while choosing and going on a trip is the risk and level of security provided, such as: physical (infrastructure), natural and human ‎environment, as well as traveling area. That is why, it is important to determine human factors that contribute to the tourist’s perception ‎of insecurity and violence in the city of Latacunga. Thus, the present investigation refers to the problem of tourists’ victimization and their ‎fear going to the city due to its violence and danger. The approaches used were the following: quantitative, documentary, field, ‎non-experimental, cross-sectional and exploratory, descriptive and correlational. The investigation results revealed that migration, ‎violence, unemployment and tourist victimization are the reasons that trigger low tourism demand in the city. In this regard, the scientific ‎information revealed that the image of insecurity that has the tourist of the canton and the perception of violence caused is simmering ‎and pretty high‎.